A comparison of physical anxiety levels in adolescent and young women with polycystic ovary syndrome and in other healthy adolescent and young women in a university hospital, Turkey. Issue 6 (31st March 2020) - Duman, Mesude; Durgun Ozan, Yeter
Abstract : Purpose: This study was conducted to investigate the Social Physique Anxiety (SPA) level in adolescent and young women with polycystic ovarian syndrome (PCOS). Design/methodology/approach: This is a descriptive study. It was conducted in Turkey. The study was conducted from January 1, 2017 to December 31, 2017. It was completed with a total of 150 young women – 75 of them had PCOS and 75 of them were healthy. Study data were collected using demographic information form and Social Physique Anxiety Scale (SPAS). Findings: The study was found that the adolescent and young women with PCOS had higher subscales and total scores for total SPAS at a statistically significant level than healthy adolescent and young women ( p  < 0.05). Practice implication: The findings of this study may be used for planning and implementing interventions in health-care practice such as screening and early treatment of SPA of women with PCOS. Originality/value: It was found that PCOS in adolescent and young women increased the SPA level. In line with these results, health professionals must be particularly aware of the potential psychosocial and health needs of adolescent and young women with PCOS.